PELATIHAN FOTO PRODUK SEBAGAI UPAYA PENINGKATAN PROMOSI UMKM ANUGRAH JAYA IBU SHINTA MALANG - Ni Putu Elvian Andreani; Lutfi Tri Atmaji; Hindam Basith Rafiqi; Wahyu Kurnia Dewi (Jurnal Abdimas Bina Bangsa, 2024)
This community service reviews the problems faced by Mrs Shinta's Anugrah Jaya MSME located in Malang. This MSME produces tempeh, cassava, banana and taro chips which are handmade and manual equipment. The lack of long-term knowledge makes it difficult for Anugrah Jaya Ibu Shinta to compete. From the observation, it was found that there was no maximum utilisation of social media. The business owner has only received messages through the whatshapp platform. Not only that, but product shots are also disproportionate and many parts are cut or not visible due to camera angle errors. This article aims to share the experience of Community Service in the form of product photo training conducted through observation and training methods. The training was conducted through 2 stages, namely the socialisation and practice stages. This photo training aims to enable Mrs Shinta's Anugrah Jaya MSME to package her kripik products in photos that look visually appealing so that they can support product sales